Respiratory outcome in late childhood after neonatal continuous negative pressure ventilation. Issue 1 (11th August 2006) - Telford, K; Waters, L; Vyas, H; Manktelow, B N; Draper, E S; Marlow, N
Abstract : Background: The outcome in late childhood for children entered into a randomised trial of continuous negative extrathoracic pressure (CNEP) versus standard respiratory management for the treatment of neonatal respiratory distress was studied. In the original trial, there were advantages in the duration of oxygen and the prevalence of chronic lung disease for those assigned to receive CNEP. Aim: To determine whether the above differences had persisted into childhood. Methods: Outpatient evaluation of children by a paediatrician using Spirometry (Vitalograph Spirometer 2120, Ennis, Ireland) and MicroRint (Micro Medical, Rochester, Kent, UK) techniques independently of the original trial. Parents completed questionnaires about their child's respiratory history and social–demographic information. Results: 133 (65%) survivors were evaluated at 9.6–14.9 years of age. The group examined were representative of the original cohort and no significant baseline differences were observed between children evaluated who had been allocated to CNEP or standard treatments. We compared Rint (before and after bronchodilator) and forced expiratory flow, volume and vital capacity between the two study groups; none were significant. Children in the standard group had received paediatric intensive care more often (p = 0.19) and were more likely to be receiving inhaled drugs for asthma (p = 0.19; all not significant). Conclusions: No important differences were found at follow-up in late childhood in respiratory outcomes for children treated with neonatal CNEP or standard treatment. Caution should be exercised, as the original trial was not powered to show these differences, but there seems to be no long-term detriment in respiratory outcomes for children treated with CNEP in the neonatal period.